The Arctic Countriesâ€™ Supply Chain Strategies in The Context of Arctic Territory Delimitation - Isabella Damdinovna Elyakova; Roman Dmitrievich Sleptsov; Alexandr Alekseevich Pakhomov; Alexandr Lvovich Elyakov; Darya Victorovna Tumanova (International Journal of Supply Chain Management, 2019)
The article discusses the supply chain strategies of the so-termed Arctic Five â€“ the Russian Federation, Canada, the USA, Norway and Denmark, which have borders in the Arctic in the context of the search for their common goals and objectives in order to develop possible ways and means to solve the main common problem â€“ the territory delimitation in the Arctic between these countries. Much has been written about the legal methods of maritime delimitation in the Arctic, but their essence is to compare the principles of â€œSectoral divisionâ€ in the Arctic with the norms of the 1982 â€œUnited Nations Convention on the Law of the Seaâ€. Meanwhile, the current international situation and the current state of the Arctic countries in relation to each other in the sphere of military power, economy, science and climate change in the Arctic, force us to consider the issue of territory delimitation in the Arctic in an extensive aspect.Â